Targeting N-doped graphene quantum dot with high photothermal conversion efficiency for dual-mode imaging and therapy in vitro. (25th June 2018) - Xuan, Yang; Zhang, Ruo-Yun; Zhang, Xiao-Shuai; An, Jie; Cheng, Kai; Li, Cheng; Hou, Xiao-Lin; Zhao, Yuan-Di
Abstract: A graphene quantum dot (GQD) is a novel carbon nanomaterial with the advantages of low cost and no pollution. It has attracted serious attention in the biomedical fields because of its stabilities and tunable fluorescence wavelength. In this manuscript, an N-doped graphene quantum dot (N-GQD) was synthesized by a hydrothermal method using citric acid as the carbon source and urea as the nitrogen source. X-ray diffraction, Raman spectroscopy, transmission electron microscopy, UV–vis absorption spectrum, and fluorescence spectrum were used to characterize the N-GQD. The results showed that the N-GQD had a uniform size of about 5 nm. The two fluorescence emission peaks, one in the visible light region showed a 49.75% quantum yield, while another in the near infrared region was 2.49%. The photothermal conversion efficiency was 62.53%, higher than any kind of carbon nanomaterial in existence today. MTT and a long-term cytotoxicity experiment confirmed that the N-GQD had low cytotoxicity. The probe also had the ability of photoacoustic response at the same time. After coupling with folic acid, it presented imaging and photothermal therapy on the cells, which has great application prospects in the early diagnosis and treatment of tumors.